Efektivitas Berkumur Larutan Madu Dan Ekstrak Kurma Ajwa Terhadap Kebersihan Gigi Dan Mulut Pada Anak Prasekolah - muunir, zainal; Putriayana, Sofiyatul; Candra Dewi, Novela Eka (Jurnal Perawat Indonesia, 2024)
Preschool children aged 3 to 6 years. Dental and oral hygiene where the teeth are in the oral cavity in a clean condition. Dental and oral hygiene can be avoided in various ways, one of which is natural mouthwash such as honey solution and ajwa date extract because it has antibacterial properties. This study aims to determine the effectiveness of gargling honey solution and ajwa date extract on dental and oral hygiene in preschool children at the PAUD Anak Sholih Pondok Pesantren Nurul Jadid The study design used quasi-experimental using Pretest-posttest Nonequivalent Control Group. Population 60 people using Total Sampling technique. Data analysis using Wilcoxon test and Mann Whitney test. Analysis of dental and oral hygiene data of preschool children before and after gargling honey solution results P-value 0.000, or P <0.05. Ajwa date extract results P-value 0.001, or P <0.05. control group P-value 0.180, or P <0.05. Which means there is a difference in the intervention group compared to the control group. Meanwhile, the Mann Whitney statistical test showed no significant difference between the two intervention groups with a value of p = 0.336 (p> 0.05). Honey solution and ajwa date extract are both effective in improving dental and oral hygiene.